Peanut Variety Performance in Florida, 2005 – 2008 - Barry Tillman; Mark Gomillion; George Person; Justin McKinney; Bill Thomas (EDIS)
SS-AGR-323, a 14-page illustrated fact sheet by Barry Tillman, Mark Gomillion, George Person, Justin McKinney, and Bill Thomas, provides data from University of Florida trials conducted in Florida at IFAS research centers located in Gainesville (Citra), Marianna, and Jay from 2005-2008. Published by the UF Department of Agronomy, July 2009.